Reading Comprehension through Blended Learning at IAIN Samarinda - Junedi Junedi; Dzul Rachman (Borneo Educational Journal (Borju), 2020)
Due to the growing need for English reading in the academic world, learners' reading abilities must be improved in order to have a better understanding of English texts. If learners grow comfortable with reading strategies, they will become more motivated to read, which will result in more exposure to foreign language information. The researchers discovered that students who were taught using Blended Learning and mobile learning had increased reading abilities in English and a more favorable attitude toward Blended Learning in reading class. The study included both quantitative and qualitative approaches. The experiment is conducted by the administration of a test to collect data on learning outcomes, while the qualitative data is collected through the use of questionnaires and interviews. IAIN Samarinda's first semester sampled 32 students. The findings were analyzed using the t-test method. It was found based on the two scores and the t-value that there was a statistically significant increase in reading for learning to use a blended learning approach. Additionally, the questionnaire and student interview data about the perspective of blended learning in reading classrooms indicated that blended learning had a favorable influence. Blended learning may be utilized to assist learning in English language lessons. The advantages of blended learning as a supplement to secondary or foreign language education will benefit students.